METHODS OF SELECTING NATIONAL MOVEMENT GAMES THAT DEVELOP PHYSICAL QUALITIES IN ACCORDANCE WITH THE AGE OF STUDENTS - Rustamov E. R. (Proximus Journal Publishing, 2024)
This article provides the necessary information about national movement games that develop physical qualities: strength, speed, agility, endurance and flexibility, and their organization.
Keywords: Physical qualities; strength; speed; agility